EXPORT PERFORMANCE ANALYSIS OF BLACK TEA (HS 090240) INDONESIA IN THE UNITED STATES MARKET - Wedari, Maharani Sri; Hendrati, Ignatia Martha (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
Tea stands as the second most consumed beverage worldwide, following water. Indonesia holds a prominent position among the largest tea-producing nations globally, with a primary emphasis on black tea production. The American market serves as a pivotal export destination for black tea, holding strategic significance in the trading dynamics of this commodity. The prevalence of black tea within the US market delineates discernible consumption patterns and interest, highlighting the United States' pivotal role in the global acceptance and dissemination of black tea commodities. The research methodology encompasses the utilization of Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Constant Market Share (CMS). This study is designed to assess Indonesia's competitive standing and advantage in exporting black tea to the United States market within a specified timeframe. The analysis outcomes reveal Indonesia's comparative advantage within this sector and illustrate fluctuations in its competitive position vis-à-vis competing nations in the US market.